Nanocatalysts: Applications in synthesis of chalcones – a review. Issue 1 (2nd January 2021) - Jain, Sapna; Kumar, Sanjeev; Lamba, Bhawna Yadav; Patra, Jeevan; Mahindroo, Neeraj
Abstract: Chalcone is one of the most versatile scaffolds with wide range of applications. It is used as a precursor for diverse classes of organic molecules. Several methods are reported for the synthesis of chalcones using conventional catalysts. Nanocatalysts are gaining attention due to their efficiency, reproducibility, cost-effectiveness, reusability, etc. This review will give an epigrammatic status of the nanocatalyst used in the synthesis of chalcone. The review also discusses methods used for the synthesis of chalcones. Graphical Abstract: